Rediscovery of a Rare Indian Liverwort, Delavayella serrata Steph. (Marchantiophyta) from Western Himalayas - Tewari, S.D.; Binwal, Neha; Joshi, Prachi; Bhandari, Manisha; Pant, Sapana; Kohli, Neha (Indian Forester, 2022)
No Abstract